Safe-haven assets, financial crises, and macroeconomic variables: Evidence from the last two decades (2000-2018) - Marco Tronzano (Journal of Risk and Financial Management, 2020)
This paper focuses on three "safe haven" assets (gold, oil, and the Swiss Franc) and examines the impact of recent financial crises and some macroeconomic variables on their return co-movements during the last two decades. All financial crises produced significant increases in conditional correlations between these asset returns, thus revealing consistent portfolio shifts from more traditional towards safer financial instruments during turbulent periods. The world equity risk premium stands out as the most relevant macroeconomic variable affecting return co-movements, while economic policy uncertainty indicators also exerted significant effects. Overall, this evidence points out that gold, oil, and the Swiss currency played an important role in global investors' portfolio allocation choices, and that these assets preserved their essential "safe haven" properties during the period examined.
Keywords: 330; gold price; oil price; safe-haven assets; Swiss Franc exchange rate